ASSESSMENT OF REFORMING THE HEALTH PROTECTION OF THE POPULATION OF RUSSIA IN RECENT YEARS - Дмитрий Григорьевич Данцигер; Сергей Николаевич Филимонов; Борис Павлович Андриевский; Константин Викторович Часовников (Медицина в Кузбассе)
An attempt is made to assess the reform of the health care system of the Russian population in recent years. To eliminate the existing problems, two alternative approaches are proposed: the first is the introduction of private medical services, starting from the birth of a person. However, neither society nor the state is ready for such an approach. The second approach is to restore the experience of Soviet, including military, medicine as soon as possible.